DISTRIBUSI TAMBAK KOTA TARAKAN BERDASARKAN INTERPRETASI CITRA SATELIT LANDSAT-TM - Cahyadi, Jimmy (Jurnal Harpodon Borneo, 2010)
The purpose of this research is to detects the distribution of rearing pond district Tarakan. Area study is coastal and sea Tarakan. Stage of this research is observation, survey secondary data survey primary data, process satellite image data and interpretation spatial distribution and area where does image composite result classification use method isoclass unsupervised classification based on satellite image interpretation landsat ETM +7. This result of study showed the distribution of rearing pond district Tarakan intepretation based citra Landsat-TM is 1.566,5 ha with dominant distribution in area west and north par island. From result ground truthing and beginning observation, condition rearing pond is divided on two that is, rearing ponds productive and rearing ponds non productive, where does condition second ratio 1.500,3 rearing ponds productive and 66,2 ha non productive.Keywords : Rearing Pond, Distribution, Citra Landsat ETM +7.